Pengaruh Fundamental Ekonomi dan Kinerja Keuangan Terhadap Kredit Bermasalah Pada Bank Syariah Di Indonesia - Soeharjoto Soekapdjo; Debbie Aryani Tribudhi; Lucky Nugroho (Fakultas Ekonomi Universitas Kadiri, 2019)
Purpose of this study is to determine economic fundamentals influence and financial performance on non-performing loans in sharia banks in Indonesia. Used quarterly panel data from 2008-2016, which came from BPS, BI, and OJK. Eleven banks used as a sample, with a purposive sampling approach. Using regression methods, with the dependent variable is NPF, and independent variable for economic fundamentals using exchange rates, inflation, GDP and financial performance with FDR, CAR, OER. Result shown that fundamental economice do not affect the NPF and OER as a financial performance has a positive and significant influence to NPF, CAR has negative and significant influence to NPF, but has no effect to FDR.